(untitled) (Edad Media. Revista de Historia, 2024)
Wills are a fundamental source of knowledge since they are individual documents whose formulas reflect the belief system and the collective mentality of an area set in specific geographical and temporal coordinates. For this reason, the will of Queen Urraca of Castille, whose life trajectory has been so timidly approached by historiography, will be analysed in this paper to deepen the knowledge of her circumstantial situation and, with it, increase both the information on the belief in the salvation of the soul through pious works and on the dynamics of the relationship between royal and ecclesiastical power in the High Middle Ages.